Study of oxygen transfer efficiency at baffled chutes - Kaya, N.; Emiroglu, M. E. (Ice Publishing, 2010)
Baffled chutes are commonly used in storm water systems, irrigation systems, canal wasteway systems, river training, and drops for energy dissipation. There is a close relationship between energy dissipation and oxygen transfer efficiency. Oxygen transfer across the air-water interface at a hydraulic structure occurs through self-aeration along the chute, and by flow aeration in the hydraulic jump at the downstream end of the structure. The oxygen concentration in surface water is a primary indicator of the water quality for human use and for the aquatic biota. This present study focused on predicting the aeration efficiency of baffled chutes. The variation of the aeration efficiency for stepped, wedge, trapezoidal and T-shaped baffle blocks was investigated in relation to chute angle, unit discharge, and chute height. The results obtained from this approach show that baffled chutes are effective for oxygen transfer. Thus, an empirical correlation predicting aeration efficiency was developed. This new equation has practical implications for predicting baffled chute aeration efficiency.
Keywords: environment; hydraulics & hydrodynamics